Reimaging a Canadian National Security Strategy - Aaron Shull (The Journal of Intelligence, Conflict and Warfare, 2022)
On November 26, 2021, Mr. Aaron Shull, Managing Director and General Counsel at the Centre for International Governance Innovation (CIGI), presented on Reimaging a Canadian National Security Strategy at the 2021 CASIS West Coast Security Conference. The presentation was followed by a question and answer period with questions from the audience and CASIS Vancouver executives. The key points discussed included CIGI’s new project to address Canada’s national security strategy gap and what it will take to accomplish the goals that could derive from the recommendations provided.